Rapid Release ODF Loaded with Ketoprofen– Tromethamine Multicomponent Crystals: Formulation and Evaluation - Indah Syahrani; Adhitya Jessica; Erizal Zaini (JSFK (Jurnal Sains Farmasi & Klinis), 2026)
Ketoprofen is a nonsteroidal anti-inflammatory drug (NSAID) with low solubility and limited bioavailability. To enhance its solubility, ketoprofen was modified into a multicomponent crystal with tromethamine using the solvent evaporation method. The ketoprofen–tromethamine multicomponent crystal was then formulated into an orally dissolving film (ODF) to produce a dosage form that rapidly disintegrates in the oral cavity. The ODF was prepared by the solvent casting method, with variations in HPMC K4M as the film-forming polymer and PEG 400, propylene glycol, and glycerin as plasticizers. The formulations were evaluated based on organoleptic properties, thickness, pH, folding endurance, moisture content, swelling index, disintegration time, and dissolution profile. The optimal formulation was identified in F07, which consisted of 2% HPMC K4M and 30% PEG 400, resulting in a film with the best physical and mechanical properties and a disintegration time of 37.21 ± 1.93 seconds. These findings indicate that the ketoprofen–tromethamine multicomponent crystal ODF improves dissolution performance and meets the criteria for fast-disintegrating dosage forms, suggesting its potential as an effective alternative for patients with swallowing difficulties.